Strain changes on the cortical shell of vertebral bodies due to spine ageing: A parametric study using a finite element model evaluated by strain measurements. (December 2013) - Lu, Yongtao; Rosenau, Eike; Paetzold, Helge; Klein, Anke; Püschel, Klaus; Morlock, Michael M; Huber, Gerd
The probability of fractures of the cortical shell of vertebral bodies increases as ageing progresses. Ageing involves all the spinal component changes. However, the effect of the spinal component ageing on the fracture risk of the cortical shell remains poorly understood. In this study, the influence of the ageing of the spinal components on cortical shell strain was investigated. A lumbar spinal specimen (L3–L5) was mechanically tested under a quasi-static axial compressive load. Clinical computed tomography images of the same specimen were used to create a corresponding finite element model. The material properties were determined by calibrating the finite element model using the L4 cortical shell strains of the anterior centre measurement site. The remaining experiment data (axial displacement, the intra-discal pressures, L4 cortical shell strain on the lateral measurement site) were used to evaluate the model. The individual ageing process of the six spinal components (cortical shell, cancellous bone, bony endplate, posterior elements, nucleus pulposus and annulus matrix) was simulated by changing their Young's moduli and Poisson's ratios, and the effect on cortical shell strain was investigated. Results show that the cortical shell strain is more sensitive to the ageing of the cortical shell and the cancellous bone than to the ageing of the nucleus pulposus, the annulus matrix, and the bony endplates and of the posterior elements. The results can help the clinicians focus on the aspects that mainly influence the vertebral cortex fracture risk factor.